Working Memory-Driven Attention in Real-World Search. (September 2018) - Jung, Shinyoung; Yoon, Yosun; Han, Suk Won
People's attention is well attracted to stimuli matching their working memory. This memory-driven attentional capture has been demonstrated in simplified and controlled laboratory settings. The present study investigated whether working memory contents capture attention in a setting that closely resembles real-world environment. In the experiment, participants performed a task of searching for a target object in real-world indoor scenes, while maintaining a visual object in working memory. To create a setting similar to real-world environment, images taken from IKEA®'s online catalogue were used. The results showed that participants' attention was biased toward a working memory-matching object, interfering with the target search. This was so even when participants did not expect that a memory-matching stimulus would appear in the search array. These results suggest that working memory can bias attention in complex, natural environment and this memory-driven attentional capture in real-world setting takes place in an automatic manner.